IVR System for three phase motor protection, Control and Alert system using GSM (International Journal of Engineering and Computer Science, 2015)
Control systems have received exceptional attention in the industrial sector as they manage and regulate various systems. This paperis focused on the development of an IVR system for three phase motor control. A new approach is proposed for designing the protection andcontrol unit of the three phase motor using the IVR systems. The main objective is to control the motor from a remote place u sing the mobileDTMF tone and also to receive the motor status feedback through SMS. GSM is found to be the most convenient, cost efficient network to beused for the transmission of the feedback signals at the motor end along with the generation of control signal by mobile DTMF. This controlsignal and the feedback SMS is transmitted through the GSM modem. Thus, this paper serves as an introduction to a new control technique ofa three phase motor which can be effectively used for industrial purposes along with providing an SMS based alert system.